Determinants Of The Demand For Real Money Balances And Its Stability In The Iraqi Economy For The Period ( 2003-2018) - Imari, Mustafa Habeebobaid Al; Aljebory, Dr. Asam Mohamed (The journal of contemporary issues in business and government, 2021)
This paper dealt with estimating and analyzing the determinants of demand for real cash balances and their stability in Iraq for the period (2003-2018).A stable demand on real cash balances function give the green light for the monetary policy maker to use money supply as an effective toolto achieve its goals. The econometric approach was used to estimate and then test the stability of the demand on real cash balances function. The stationary test confirmed that some of our variables are stationary at level and others at the first difference. As our co-integration test revealed a long run relationships between the independent variables (exchange rate, Consumer price index, and Gross domestic product) and the real cash balances. According to that the ARDL model was used to estimate the short and the long run coefficients and the error correction parameter by using Eviews11. The results of the estimated model confirmed our hypothesis (The stability of the demand of real cash balances) as the results of CUSUM, and CUSUM SQ shows. This means the success of using money supply as an effective tool by the monetary policy maker. The ARDL results reflects the significant of the independent variables parameters on the short and the long run economically and statistically. The adjustment coefficient was -0.20 which confirm the stability of the model if departed from the equilibrium level and will return back in 5 quarters. The model shows high capability in tracking the historical data. This confirmed the forecasting merit of the model. Five different scenarios postulated to simulate the answer to the What if question for the period 2019-2025. The result of the forecast shows strong sensitivity of the demand of real cash balances to the large shock in the Exchange rate, Consumer price index, and the contraction of the GDP. The combined effect of the strong shock in the independents variable will force the public to abandon the local currency and replace it with US dollar. This will weakened the effectiveness of using the money supply as an effective tool of the monetary policy. Acknowledgment Al- MustaqbalUniversity College